Pedestrian accessibility of services as a measure of territorial cohesion at the neighbourhood level - Damurski, Lukasz; Pluta, Jacek; Zipser, Wawrzyniec (Bulletin of Geography. Socio-economic Series, 2020)
Territorial cohesion, despite its initial ambiguity, has been successfully implemented in national and regional policies across the EU. However, its operationalisation on the local level remains a major challenge. This paper asks whether pedestrian accessibility of services and public transport nodes can be used as a measure of territorial cohesion at the local level. The presented research was conducted in 2016–19 in five neighbourhoods in Poland representing various settlement contexts: large cities, medium-sized towns and suburban areas. It adapted particular indicators of territorial cohesion established by ESPON to the neighbourhood scale. The highest levels of territorial cohesion expressed by users’ satisfaction were achieved in a neighbourhood in a medium-sized town, whereas in geographical terms, territorial cohesion reached higher levels in large cities. Despite those differences, the proposed research method based on pedestrian accessibility offers quantifiable and comparable results on territorial cohesion on the neighbourhood level.